PEMAHAMAN DAN IMPLEMENTASI KEMAMPUAN KONSELING BERBASIS KOMUNITAS MAHASISWA BPI UIN SU MEDAN - Misrah Misrah; Muhammad Hambali (JURNAL ILMIAH EDUNOMIKA, 2024)
Counseling is a process of providing assistance to individuals who need it from a professional. Counseling services are provided to help individuals who are facing problems in their lives. There are several problems that arise in the understanding and implementation of counseling for students. One of the problems is students' lack of understanding of the importance of counseling. lack of awareness of counseling for some students. Limitations in providing adequate counseling services, both in terms of the number of counselors and supporting infrastructure. This type of research is descriptive qualitative research with a case study approach. The results of the research show that Islamic Extension Guidance (BPI) students at the Faculty of Da'wah and Communication, UIN North Sumatra have a good understanding of counseling and are able to implement counseling techniques well. However, there are still some of them who do not understand counseling practically, their understanding is still only theoretical. In terms of implementing counseling, BPI UIN SU students are also able to implement counseling techniques well. However, in this case there is still a need for more special training regarding counseling organized by the department for students so that they can be more professional in conducting counseling. And there are several obstacles for students in conducting counseling, including clients who come under coercion from other people, not with their own wishes, there are clients whose personalities cannot be predicted, making it difficult to determine the right approach technique in counseling.